Fabry Disease - literature review - Wdowiak, Krystian; Maciocha, Agnieszka; Wąż, Julia; Witas, Aleksandra; Muzyka, Adrian; Rydzek, Julia; Gardocka, Ewa (Journal of Education, Health and Sport, 2024)
Introduction and objective: Fabry disease (FD) is a rare lysosomal storage disorder that can manifest in classical and atypical forms, with the latter being more common. It results from deficient alpha-galactosidase activity, leading to the accumulation of globotriaosylceramide (Gb3), causing inflammation, cellular damage, and mitochondrial dysfunction. The aim of this publication is to discuss various aspects of Fabry disease based on the latest literature. Review Methods: The PubMed database was searched for scientific articles where the terms "Fabry disease" or "FD" appear in the title, abstract, or keywords. The focus was on articles published between 2017 and 2024, although in some cases, older sources were consulted when more recent data was lacking. Brief Description of the State of Knowledge: The Fabry disease occurs with a frequency between 1:40,000 and 1:117,000 live male births. Symptoms include proteinuria, kidney failure, hypertrophic cardiomyopathy, valve defects, peripheral neuropathy, and gastrointestinal issues. The disease affects life expectancy, primarily due to cardiovascular complications. Early diagnosis is often delayed due to non-specific symptoms, and prognosis tends to be worse in males. Current treatments include enzyme replacement therapy (ERT), chaperone therapy with migalastat, and second-generation ERT. Summary: Given the rarity of Fabry disease, research is limited, and there is a need for more studies to explore novel therapeutic options that could improve patient quality of life and mitigate the disease's complications.